Assessing Criminal Penalties in Marriage Law: a Comparative Study of Policy Frameworks within Indonesian and Malaysian Legislation - Sirait, Adi Syahputra; Harahap, Nurhotia; Hidayat, Taufik; Harahap, Risalan Basri (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
This article examines the policy on criminal sanctions in Islamic marriage law in Indonesia and Malaysia, focusing on a comparative analysis between the two countries. The main objective of this study is to understand how both countries, with their Muslim-majority populations, formulate and apply criminal sanctions in cases of violations of Islamic marriage law. This research employs a library research methodology. The primary sources of data for this study include Law No. 1 of 1974, the Compilation of Islamic Law, the Federal Territories Islamic Family Law Enactment, and Islamic law. The findings of this study indicate that although Indonesia and Malaysia share a common foundation in Sharia law, there are significant differences in the application of criminal sanctions related to Islamic marriage. In Indonesia, the policy on criminal sanctions is more influenced by the secular national legal system, while in Malaysia, Sharia law plays a more dominant role in the state judiciary system. The review of Islamic law related to the application of criminal sanctions for violations of marriage laws remains weak in its implementation. Therefore, stricter sanctions should be established for violators to provide a significant deterrent effect. This approach aligns with al-Ghazali's concept of maslahah, which prioritizes good and avoids harm (mafsadah).